Hyoid Bone Syndrome: A Retrospective Review of 84 Patients Treated with Triamcinolone Acetonide Injections. (March 2013) - Stern, Noah; Jackson-Menaldi, Cristina; Rubin, Adam D.
Objectives: We present a cohort of patients with hyoid bone syndrome who were treated with injections of triamcinolone acetonide (40 mg/mL), in order to raise awareness of this condition, validate its existence, and demonstrate the efficacy of this treatment. Methods: We performed a retrospective chart review of patients who were given a diagnosis of and treated for hyoid bone syndrome by the senior author (A.D.R.) between 2006 and 2009. Results: Eighty-four patients met the inclusion criteria. All patients presented with throat pain and had tenderness of 1 (63%) or both (38%) greater cornua of the hyoid bone. Seventy-four percent of the patients had complete resolution of symptoms with injection of the affected side(s), 15% had a partial response, and 10% had no response. One patient had a recurrence at 3 months and chose not to receive another treatment. Forty-five of the 62 patients with a complete response required only 1 injection. Forty-three patients (51%) also complained of dysphonia, only 5 of whom had additional laryngeal disorders that accounted for the dysphonia. Conclusions: Hyoid bone syndrome should be considered in patients who present with throat pain. Injection of triamcinolone into the affected greater cornu can confirm the diagnosis and resolve symptoms. A positive response to triamcinolone injection may obviate the need for additional testing and procedures.